Indikasi Ujaran Kebencian Netizen dalam Kolom Komentar Akun Instagram Selebgram Azizah Salsha: Kajian Linguistik Forensik - Mardiah, Radiatul; Ermanto, Ermanto (TSAQOFAH, 2026)
Although hate speech on social media has been widely examined, studies that specifically address indications of hate speech in the comment sections of particular Instagram influencer accounts remain limited. This study aims to describe (1) the types of hate speech and (2) the linguistic units that realize hate speech in the comment section of the Instagram account of influencer Azizah Salsha. This qualitative study employed a descriptive method, with data consisting of sentences or utterances by netizens that contained hate speech. The main research instrument was the researcher, assisted by note-taking, while data were collected through observation and reading methods using note-taking techniques. Data validity was ensured through triangulation, and data were analyzed by classifying and grouping the utterances based on the types of hate speech and their linguistic units. The findings show that hate speech in the comment section of the Instagram account of Azizah Salsha appears in various forms, with the most frequent type being insulting expressions (66 utterances), followed by defamation and dissemination of false information (13 utterances), incitement (9 utterances), provocation (7 utterances), and blasphemy (2 utterances). The most frequently occurring linguistic unit realizing hate speech was the sentence level (41 utterances), followed by phrases (35 utterances), clauses (23 utterances), and words (11 utterances). These findings contribute to the development of linguistic studies and broaden understandings of language use practices by netizens in digital spaces. The study concludes by emphasizing the importance of polite language awareness in social media interactions, with theoretical implications for enriching the literature on hate speech in social media and practical implications for the public and digital platform managers in fostering healthier communication spaces.